The effect of the simple soroban application on students’ mathematics learning outcomes - Rima Agustina; Nina Ikhwati Wahidah; Irma Ayuwanti; Tim Bordasch (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Islam Malang, 2026)
Mathematics learning in junior high schools is predominantly dominated by conventional, teacher-centered instruction, which often limits students’ active participation and inhibits meaningful conceptual understanding. As a result, many students experience persistent difficulties in mastering basic arithmetic concepts. To address the issue, the study introduces the Simple Soroban application as a digital abacus-based learning medium that provides visual, interactive, and concrete representations of integer operations. Therefore, the study aims to examine the effect of using the Simple Soroban application on seventh-grade students’ mathematics learning outcomes, particularly in the integer operations study, which employed a quantitative approach using a posttest-only control group design. The population consisted of all seventh-grade students of SMP Negeri 2 Purbolinggo. Samples were selected through stratified random sampling, resulting in an experimental group taught using the Simple Soroban application and a control group taught using conventional teaching methods. Data were collected using a multiple-choice test that had been tested for validity, reliability, difficulty level, and discrimination index. The data were analyzed using normality tests, homogeneity tests, and an independent sample t-test with SPSS 26 and Microsoft Excel 2010. The findings revealed a statistically significant difference in mathematics learning outcomes between the two groups, indicated by a calculated t-value of −2.742 exceeding the critical t-value of 2.002 at a significance level of 0.05. These results suggest that digital abacus-based learning media can serve as an effective instructional alternative to improve students’ understanding of integer operations. However, this study was limited to one school and one mathematical topic, which may restrict the generalizability of the findings.